Компьютерное моделирование в исследованиях и разработке измерительных информационных систем - Мазманян, Р.О. (Технічна електродинаміка, 2011)
A method of computer aided structural, mixed structural/schematic and schematic simulation for measuring systems with predictable properties design is presented. Here we demonstrate the proposed technique application on extremal automatic control system simulation. The application itself includes synthesis of the structures set up - a model of the object with a single maximum value of static characteristics and the actual controller with a synchronous detector which determines the gradient of the controlled variable to a control signal. Also we report obtained results of computational experiments and present the gradual transition from the structural to a mixed model.